Ethiopia's Infrastructure : A Continental Perspective - Foster, Vivien; Morella, Elvira (World Bank, Washington, DC, 2017)
Infrastructure contributed 0.6 percentage points to Ethiopia's annual per capita gross domestic product (GDP) growth over the last decade. Raising the country's infrastructure endowment level to that of the region's middle-income countries could lift annual growth by an additional 3 percentage points. This will represent a significant boost over the growth performance of the mid-2000s, which averaged around 5 percent. The Africa Infrastructure Country Diagnostic (AICD) has collected and analyzed extensive infrastructure data for more than 40 Sub-Saharan countries, including Ethiopia. The results are presented in reports on various infrastructure sectors Information and Communication Technologies (ICT), irrigation, power, transport, water and sanitation and policy areas, including investment needs, fiscal costs, and sector performance. This country report presents the key AICD findings for Ethiopia. This will allow its infrastructure situation to be benchmarked against that of other African nations that, like Ethiopia, are low-income countries, with particular emphasis on immediate regional neighbors in East Africa. Several methodological issues should be borne in mind. First, the cross country nature of the data collection creates an inevitable time lag. The period covered by the AICD runs from 2001 to 2006. Most technical data are presented for 2006 (or the most recent year available), while financial data typically are averaged over the available period to smooth out the effect of short term fluctuations. Second, cross country comparisons require standardization of the indicators and the analysis to ensure consistency. Therefore, some of the indicators may be slightly different from those that are routinely reported and discussed at the country level. During the 2000s, Ethiopia's annual economic growth has averaged 4.8 percent, compared with only 0.5 percent in the previous decade. Notwithstanding this improvement, current annual growth levels still fall short of the sustained 7 percent needed to meet the Millennium Development Goals. Improved structural and stabilization policies generated an estimated 4.2 percent of Ethiopia's improved per capita growth performance during the 2000s, and improvements in the country's infrastructure platform over that period contributed up to 0.6 percentage points to growth. This was due almost entirely to the introduction of mobile telephony in Ethiopia. Simulations suggest that if Ethiopia's infrastructure platform could be improved to the level of the African leader, Mauritius, annual per capita growth rates could increase by 3.8 percent. This potential impact would come equally from improvements to transport, power, and ICT infrastructure.